The Effect Of Work Discipline And Work Environment On Head Office Employee Performance Of PT. Kurnia Boga Narayan West Jakarta - Husain, Bachtiar Arifudin; Santoso, Arif Budi; Krisyanto, Edy (Sekolah Tinggi Agama Islam Darussalam Kunir, 2025)
The purpose of this study was to determine the effect of work discipline and work environment on employee performance at the Head Office of PT Kurnia Boga Narayan, West Jakarta. The method used is a descriptive quantitative method. The sampling technique uses saturated samples, the number of samples is 90 respondents. The analysis techniques used are validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, linear regression analysis, correlation coefficient analysis, determination coefficient analysis, partial significance test (t test), simultaneous significance test (f test). the results of this study are that work discipline has a positive and significant effect on employee performance with a value of (2.389> 1.661) and sig. 0.000 <0.05 with a probability level of 5% and the work environment has a positive and insignificant effect with (1.688> 1.661) sig. value 0.095> 0.05 with a probability level of 5%. Work discipline and work environment have a regression value of Y = 18.589 + 0.355 X1 + 0.113 X2. The coefficient of determination is 7% while the remaining 93% is influenced by other factors. The f test obtained a value of (3.283 > 3.091) and sig. 0.042 < 0.05 with a probability level of 5%.